Monitoring dispersion of carbon nanotubes in a thermosetting polyester resin - Battisti, Andrea; Skordos, Alexandros A.; Partridge, Ivana K. (Elsevier Science B.V., Amsterdam., 2009)
The paper concerns the initial steps in the preparation of carbon nanotube containing nanocomposites of an isophthalic unsaturated polyester resin, prior to cure. Developments in the nature of the rheology of the liquid samples were monitored as a function of the level of energy introduced via ultrasonic horn mixing and related to microscopic observations. On-line sampling, coupled with off-line viscosity measurements, is compared with on-line measurements of electrical resistivity of the mixture, in terms of the relative suitability of these techniques for real-time monitoring of nanofiller dispersion in the liquid mixtures. The shear thinning parameter, N, derived from fitting Carreau model to the shear viscosity data, appears to provide a good qualitative indicator of the state of nanotube dispersion in the sample.
Keywords: Carbon nanotubes; Unsaturated polyester matrix; Electrical properties; Rheology; Dispersion